Phosphorus removal from eutrophic waters with an aluminium hybrid nanocomposite - Oliveira, M. (2012)
An excess of phosphorus (P) is the most common cause of eutrophication of freshwater bodies. Thus, it is imperative to reduce the concentration of P to prevent harmful algal blooms. Moreover, recovery of P has been gaining importance because its natural source will be exhausted in the near future. Therefore, the present work investigated the removal and recovery of phosphate from water using a newly developed hybrid nanocomposite containing aluminium nanoparticles (HPN). The HPN-Pr removes 0.80 ± 0.01 mg P/g in a pH interval between 2.0 and 6.5. The adsorption mechanism was described by a Freundlich adsorption model. The material presented good selectivity for phosphate and can be regenerated using an HCl dilute solution. The factors that contribute most to the attractiveness of HPN-Pr as a phosphate sorbent are its moderate removal capacity, feasible production at industrial scale, reuse after regeneration and recovery of phosphate.